Role of community pharmacists in the safe and effective use of complementary and alternative medicine in the Middle East: A scoping review - Farah Naja; Maiss Ahmad; Hibeh Shatila; Katia Hazim N. Abu Shihab; Sally Naalbandian; Roba Saqan; Hamzah Alzubaidi; Mohamad Ali Hijazi (PLoS ONE, 2025)
Background Community pharmacists (CPs) play a crucial role in promoting safe use of Complementary and Alternative Medicine (CAM). This scoping review examined existing evidence on the role of CPs in CAM in the Middle East, a region harboring one of the fastest growing markets of CAM. Methods A comprehensive search of nine electronic databases was conducted to identify relevant studies published between 2000 and 2025. A total of 155 studies met the inclusion criteria. Key study characteristics were extracted using a standardized data extraction form. Thematic analysis of findings and recommendations was carried out using NVivo software to identify common patterns, themes, and gaps in the literature. Results The studies primarily used quantitative cross-sectional designs and were predominantly led by academic institutions. International and regional collaborations were scarce. Over the past 25 years, there has been a notable rise in the annual number of published papers; however, this upward trend was not reflected in the impact factors of the journals in which these papers appeared. The thematic analysis revealed three main themes: (1) Opportunities, including pharmacists’ positive attitudes and willingness to take on active roles in CAM; (2) Challenges, such as knowledge gaps, poor reporting practices, logistical barriers to counseling, weak regulatory oversight, and misinformation driven by media; and (3) Recommendations, targeting improvements in practice, education, and policy. Conclusions The review findings suggest the need for studies to diversify their designs and strengthen cross-sector collaborations. To enhance CPs’ role in ensuring the safe use of CAM, coordinated, evidence-based strategies are required. These should integrate professional development, regulatory reform, and targeted public education, ultimately supporting CPs in delivering informed, patient-centered CAM services.